Does the clerkship/internship in psychiatry affect medical students' level of knowledge about schizophrenia, attitudes, and beliefs toward schizophrenia and other mental disorders?. Issue 4 (12th June 2022) - Akpinar Aslan, Esma; Batmaz, Sedat
Abstract: Undergraduate medical students' attitudes and beliefs toward mental illnesses are a crucial phenomenon as these students will be care providers of the future. The current study aimed to analyze whether the psychiatry clerkship/internship affects these students' level of knowledge about schizophrenia as well as their attitudes and beliefs toward schizophrenia and other mental illnesses. A total of 158 medical students, 92 in their fifth year and 66 in their sixth year, were included in the study. The participants completed the Knowledge About Schizophrenia Questionnaire (KASQ), Beliefs toward Mental Illness Scale (BMI), and Attitudes toward People with Mental Disorders Scale (APMDS) before and after the psychiatry clerkship/internship. The KASQ and APMDS total scores were significantly higher whereas BMI and BMI‐Dangerousness subscale scores were significantly lower after the clerkship/internship in psychiatry. Postclerkship/internship KASQ total scores were negatively correlated with BMI total scores and BMI‐Dangerousness subscale scores. Additionally, BMI total scores and APMDS total scores were also negatively correlated. Although the change in KASQ scores was significantly associated with the decrease in BMI total scores after the clerkship/internship, it was not associated with the increase in APMDS total score in the hierarchical multiple linear regression analysis. In conclusion, the present study revealed that knowledge about schizophrenia and attitudes and beliefs toward mental illnesses improved significantly after the clerkship/internship in psychiatry. While improvement in medical students' knowledge about schizophrenia and mental illnesses is a predictor of the decrease in negative beliefs about mental illnesses, a similar relationship was not found regarding attitudes. This study not only provides information about the relationship between knowledge about schizophrenia and attitudes and beliefs about mental illness but also highlights the need to consider the multifactorial nature of attitudes when developing intervention programs for medical students.